Relationships of Bone Mineral Density to Whole Body Mass, Fat Mass and Fat-free Mass in Long-term Survivors of Acute Lymphoblastic Leukemia in Childhood. Issue 1 (January 2021) - Athale, Uma H.; Marriott, Christopher J.C.; Cranston, Amy; McDonald, Paula; Webber, Colin E.; Farncombe, Troy H.; Barr, Ronald D.
Abstract : Body size influences bone mineral density (BMD) in health. Relationships of BMD with body mass index, fat mass (FM), fat-free mass, and appendicular lean mass were explored in acute lymphoblastic leukemia (ALL) survivors (n=75; 41 males; 45 standard risk ALL) >10 years from diagnosis. Dual energy radiograph absorptiometry performed body composition analysis. Relationships were assessed by regression analyses and Pearson correlation coefficients ( r ). Twenty subjects (26.3%) were osteopenic; lumbar spine (LS) BMD Z score <−1.00. Age at diagnosis, sex, ALL risk-category, type of post-induction steroid or cranial radiation did not correlate with LS or whole body (WB) BMD. Body mass index correlated significantly with LS BMD ( r =0.333, P =0.004) and WB BMD ( r =0.271, P =0.033). FM index (FM/height²) Z score showed no significant correlation with LS or WB BMD. Fat-free mass index Z score correlated strongly with LS BMD ( r =0.386, P =0.013) and WB BMD ( r =0.605, P <0.001) in males but not in females. The appendicular lean mass index, a surrogate for skeletal muscle mass, correlated significantly with LS BMD ( r =0.367, P =0.018) and WB BMD ( r =0.604, P <0.001) in males but not in females. Future studies to evaluate interventions to enhance BMD focused on improving body composition particularly skeletal muscle mass are warranted. Abstract : Supplemental Digital Content is available in the text.